Microbiological analysis of phytoterapic symptoms (hedera helix l.) for adult/ pediatric use marketed in the city of Teresina-PI (Research, Society and Development, 2022)
According to DRC No. 26/2014, herbal medicines are a product obtained from active vegetable raw material, with a prophylactic, curative or palliative purpose. The need for microbiological control of these products is important, mainly due to the safety, efficacy and acceptability of these products. The objective of this work was to evaluate the microbiological control of syrups based on the plant Hedera helix L. Two brands of herbal syrups were analyzed. Two dilutions (1:10 and 1: 100) were carried out with neutralization of the preservatives, and subsequent transfer to the enrichment broth, and incubation in the oven at 37 ° C for 24hrs. For the total counting of mesophilic microorganisms, the in-depth method was used for molds and yeasts using a surface method and for the detection of microorganisms, the presence of Escherichia coli, Staphylococcus aureus, Salmonella sp. In sample 1, there was growth of white and yellow colonies at the dilution 10¹, and for dilution at 10², there was no microbial growth. However, for sample 2 at the dilution of 10¹, there were countless small yellow colonies with Gram-positive cocci, while at the 10² dilution there was no growth. For the counting of molds and yeasts, in sample 1 in both dilutions, did not identify fungal form and sample 2 in dilution 10¹ found countless mucoid colonies, with brownish coloration. The present work demonstrated the need for microbiological control of herbal products since the safety, efficacy and acceptability of these products need to be maintained to avoid changes in their physical and chemical properties and to avoid the risk of infection for their users.